Child and caregiver reported problems in using asthma medications and question-asking during paediatric asthma visits. (29th May 2013) - Sleath, Betsy; Carpenter, Delesha M; Beard, Ashley; Gillette, Christopher; Williams, Dennis; Tudor, Gail; Ayala, Guadalupe X
Abstract: Objectives: The objectives of the study were to describe the extent to which lay caregivers and children who reported asthma medication problems asked medication questions during their medical visits. Methods: Children with asthma ages 8 through 16 years and their caregivers were recruited at five paediatric practices and their medical visits were audiotape recorded. Children were interviewed after their medical visits and caregivers completed questionnaires. A home visit was conducted 1 month later. Generalized estimating equations were used to analyse the data. Key findings: Two hundred and ninety six families participated. Among those caregivers who reported asthma medication problems, only 35% had asked at least one medication question during the visit. Among children who reported asthma medication problems, only 11% had asked at least one medication question during their consultation. Caregivers and children who reported a problem with their asthma medications were significantly more likely to have asked medication questions if providers had asked more questions about control medications. Children who reported higher asthma management self-efficacy were significantly more likely to have asked an asthma medication question. Conclusions: Only one in three caregivers and one in 10 children who reported an asthma medication problem asked a question during their medical visits and many still reported these problems 1 month later. Pharmacists should encourage caregivers and children to report problems they may be having using their asthma medications.